VARIOUS SALINITY EFFECTS ON NILE TILAPIA SEEDS (OREOCHROMIS NILOTICUS) GROWTH RATE IN ARTIFICIAL SEAWATER - Satiti, Cinca Hayyu Putri; Faqih, Abd. Rahem; Mahmudi, Mohammad (Directorate of Research and Community Service (DRPM), 2025)
Nile tilapia (Oreochromis niloticus) is a euryhaline fish that can live in both freshwater and brackish waters. This research aims to determine the optimal salinity for the growth of Nile tilapia in an effort to revitalize abandoned ponds in the coastal areas of Java Island, Indonesia. The research was conducted at the Laboratorium Perikanan Air Tawar Sumberpasir Malang. The salinity treatments given were 0 ppt (control), 7 ppt, 14 ppt, and 21 ppt. The parameters observed include Absolute Growth, Specific Growth Rate, Feed Conversion Ratio (FCR), and water quality. The results show that the best Absolute Growth in Weight and Length occurred at the 7 ppt treatment with values of 8.82±0.40g and 2.45±0.16 cm. The best Specific Growth Rate for weight and length in the 7 ppt treatment were 97±0.07% and 67±0.08%, respectively. The best feed conversion in the 0 ppt treatment (1.28±0.49%). The water quality in this study was already optimal according to the Quality Standards for Nile Tilapia Farming in Indonesia.